Analisis Tindakan Perawatan Korektif Komponen Chain coupling Pada Mesin Distributing conveyor di PT. Perkebunan Nusantara VIII - Pratama, Fajar Wahyu; Putra, Ananda Yhuto Wibisono (Universitas Muhammadiyah Tangerang, 2025)
The palm oil industry is an industry that produces palm oil. In palm oil processing, some stages have used machines. One of the machines in the palm oil industry is the distributing conveyor. The function of the distributing conveyor is to carry and distribute fresh fruit bunches from the fruit elevator to the digester. Maintenance is an activity carried out to repair or restore something that is damaged or experiencing problems. The main objective of this research is to analyze the component damage on the distributing conveyor machine and perform Corrective Maintenance on the machine through component replacement on the distributing conveyor machine. This research was conducted with a qualitative approach using the ex post facto method and the results were analyzed descriptively qualitatively. For data collection techniques, namely observation, literature study, and interviews. The results of the discussion are that when the Sprocket component on the distributing conveyor machine is damaged, signs such as vibration in the engine, abnormal sound, and decreased engine performance will appear and the effect when it is still forced to be used is to reduce the effectiveness of power transfer and the appearance of vibration or rumbling in the chain. In Corrective Maintenance actions there are several stages carried out, namely making component designs, modifying components, and replacing components. After the replacement of the new sprocket, the engine can function normally again, and the signs or disturbing effects have been resolved. Keeping machinery in good condition through timely Corrective Maintenance is critical to improving efficiency, productivity, and safety in industrial environments. Corrective Maintenance, although it tends to be more expensive, remains a part of the machine maintenance strategy to achieve optimal production results.